2021
DOI: 10.1080/1743727x.2021.1963226
|View full text |Cite
|
Sign up to set email alerts
|

Combining statistical and machine learning methods to explore German students’ attitudes towards ICT in PISA

Abstract: In our age of big data and growing computational power, versatility in data analysis is important. This study presents a flexible way to combine statistics and machine learning for data analysis of a large-scale educational survey. The authors used statistical and machine learning methods to explore German students' attitudes towards information and communication technology (ICT) in relation to mathematical and scientific literacy measured by the Programme for International Student Assessment (PISA) in 2015 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 94 publications
1
5
0
2
Order By: Relevance
“…Starting with the analysis of the results obtained, it was generally observed that the assessment of ICT use and engagement in the educational environment was medium-high. This is in line with other studies [5,[45][46][47][48][49][50]. It is true that certain aspects were below the overall average, as in the case where students forget about time when using electronic devices or where they exchange solutions to problems with digital devices using the Internet.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Starting with the analysis of the results obtained, it was generally observed that the assessment of ICT use and engagement in the educational environment was medium-high. This is in line with other studies [5,[45][46][47][48][49][50]. It is true that certain aspects were below the overall average, as in the case where students forget about time when using electronic devices or where they exchange solutions to problems with digital devices using the Internet.…”
Section: Discussionsupporting
confidence: 91%
“…The main research on the motivation generated by ICT in adolescents is related to education, especially in how the use of ICT in students, at home and at school, influences the performance of reading comprehension [5,45,46], mathematics [47,48] and science [47][48][49][50]. In these three domains or areas of knowledge, there are differences in academic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La ciencia de datos permite identificar, clasificar y evaluar los datos de las variables con el propósito de descubrir información relevante de los fenómenos (Chadaga et al, 2021;Lezhnina & Kismihok, 2021). En el aprendizaje automático, las técnicas sobre la regresión lineal y el árbol de decisión facilitan el análisis sobre las variables independientes y dependientes para establecer las condiciones y relaciones de los eventos predictivos y descriptivos (Lezhnina & Kismihok, 2021).…”
Section: E Ciencia De Datosunclassified
“…De acuerdo con Chadaga et al (2021), la técnica de regresión lineal tienen un papel fundamental en el campo de la medicina debido a que ésta permite analizar y predecir el comportamiento de las enfermedades y virus como el SARS-CoV-2. Incluso, esta técnica de la ciencia de datos permite conocer el nivel de influencia entre las variables de estudio por medio de la división de la muestra en la sección de entrenamiento y evaluación (Chadaga et al, 2021;Lezhnina & Kismihok, 2021;Salas-Rueda, 2021).…”
Section: E Ciencia De Datosunclassified